Influence of desert sand on the mechanical properties of concrete subjected to impact loading - Haifeng, Liu; Jurong, Ma; Yiying, Wang; Jianguo, Ning (Acta mechanica solida Sinica, 2017)
A74-mm-diameter Split Hopkinson pressure bar was used to carry out the dynamic compression experiment of concrete made of desert sand. The dynamic failure processes of concrete different in specimen size, impact velocity, desert sand replacement ratio, size and volume content of coarse aggregate were simulated. Research results showed that concrete made of desert sand had size-effect and was rate-dependent. The peak stress of concrete made of desert sand declined with the minimum size of coarse aggregate. However, the peak stress of concrete made of desert sand increased first, and then declined with the volume content and maximum size of coarse aggregate.